Klasifikasi Masyarakat Wajib Pajak Di Kabupaten Simalungun Menggunakan Metode Naive Bayes - Idris Hanafia Lubis; P Poningsih; Ilham Sahputra Saragih (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2019)
Regional tax is a tax set by the regional government with regional regulations, the collection of which is carried out by the regional government and the subsequent results are used to finance the expenditure of regional governments in implementing governance and development in the region. Poor knowledge and understanding of taxes received by the community in paying taxes. The quality of good tax knowledge will greatly affect the smooth running of taxpayers in fulfilling their tax obligations. In this study, the method used in measuring the free or not of taxpayers in Simalungun District uses the method of using Naive Bayes. The parameters used are Modernization of Tax Administration System, Taxation Information Session, Taxation of Awareness, Tax Sanctions, Taxpayer Compliance. The data used in this study provides questionnaires to people who have a type of business in Simalungun District specifically in Java. It is expected that the results of this study can help the government specifically the Regional Revenue Service to understand the understanding and responsibility of the community in fulfilling their tax obligations.